Classroom Simulations for Teaching Production Control in Nonrepetitive Contexts: Insights for Theory and Practice. (1st September 2020) - Thürer, Matthias; Cole, Rosanna; Hanna, Mark D.; Protzman, Charles W.
ABSTRACT: When introducing production control solutions, most textbooks focus on a to‐stock, repetitive context. In response, we extend the classical match‐and‐dice game, which also assumes a repetitive context, to teach complexities that emerge in a nonrepetitive setting, such as the appearance of direct and indirect load, and to introduce appropriate production control solutions (e.g., Con stant W ork‐I n‐P rocess [ConWIP] and Co ntrol of Ba lance by Ca rd Ba sed Na vigation [COBACABANA]). Two field tests were used to prove the playability of our game and assess its teaching effectiveness using postgame scores and self‐assessment. Both test results give support to our game and highlight that it helps students to understand complex production control issues. Applying the simulation as part of an iterative design process not only ensured the pragmatic validity of our design, but also provided important insights on the production control systems being taught. During the application, we encountered several issues associated with the implementation of these production control systems in practice. In terms of theory, applying the simulation showed that there is a change in mindset required when switching from Kanban to COBACABANA, and physics synchronization is essential for logistics synchronization.